The influence of behavior work facilities and organizational commitment on improving employee performance of PT Bank Mandiri Medan - Hilman Saidi Raja Bakkol Harahap; Arham Syaukani; Dea Egano Okviar Napitupulu (Institute of Computer Science (IOCS), 2023)
This study aims to identify the positive and significant influence, both collectively and partially, between employee behavior, work facilities, and organizational commitment to the performance of PT's employees. Bank Mandiri Imam Bonjol Medan. This research uses quantitative methods with the type of research using primary data and secondary data. The population in this study consisted of 56 employees of the Imam Bonjol Bank Mandiri in Medan as a research sample. The data analysis technique used is multiple linear regression and partial regression with SPSS 20.0. The results of the regression analysis showed that the employee behavior variable received the results of the analysis of 0.039, so it can be concluded that employee performance is positively and significantly influenced by employee behavior. The variable of the work device has a positive and significant effect on employee performance. The results showed that the variables employee behavior, work facilities, and organizational engagement together had a positive and significant effect on employee performance. So the conclusion of this study is that the employees of PT. Bank Mandiri Medan understands what they must develop to improve performance and career to a higher level so that the goals of employees and the company are achieved faster.